Caracterização hidroquímica de águas subterrâneas aliada ao uso de óxido de grafeno reduzido para adsorção de herbicidas - Soares, Gabriela Borges (2019)
Studies of groundwater are becoming more frequent as drinking water shortages are increasing. The current study aims to analyze groundwater physicochemical parameters, to investigate the presence of herbicides glyphosate, imazethapyr and 2,4-dichlorophenoxyacetic acid (also known as 2,4-D), besides evaluating the efficiency of the use of reduced graphene oxide (rGO) in the removal of these herbicides from water. Groundwater of Alegrete, Agudo, Dona Francisca, Faxinal do Soturno, Nova Palma and Santa Cruz do Sul - RS municipalities were characterized. Adsorption tests of the herbicides were carried out in water using rGO. When considering the adsorption test results, it can be stated that the rGO was efficient in the simultaneous adsorption of the herbicides imazetapir and 2,4-D, reaching values of 93% and 99% of removal, respectively. Overall, 58 well samples were collected and analyzed in duplicate at different times of the year. The maximum residue levels (MRL) were used as reference limits by the Consolidation Ordinance No. 005/2017 and the CONAMA Resolution 396/2008. One well had a high concentration of glyphosate. Concentrations above the MRL for fluoride were found in eleven wells. One well surpassed MRL for nitrate. Four wells had concentrations above the MRL for sodium. For the arsenic concentrations above the MRL were found in four wells, for the selenium three wells had concentrations above the MRL. Most samples, 42 wells, presented all the chemical parameters within the MRL. Therefore, 16 wells had one or more parameters above MRL, indicating the need for greater attention in the hydrochemical aspect for human consumption.